The European Academy of Andrology (EAA) ultrasound study on healthy, fertile men: Scrotal ultrasound reference ranges and associations with clinical, seminal, and biochemical characteristics. (19th January 2021) - Lotti, F; Frizza, F; Balercia, G; Barbonetti, A; Behre, HM; Calogero, AE; Cremers, JF; Francavilla, F; Isidori, AM; Kliesch, S; La Vignera, S; Lenzi, A; et al.
Abstract: Background: Scrotal color Doppler ultrasound (CDUS) still suffers from lack of standardization. Hence, the European Academy of Andrology (EAA) has promoted a multicenter study to assess the CDUS characteristics of healthy fertile men (HFM) to obtain normative parameters. Objectives: To report and discuss the scrotal organs CDUS reference ranges and characteristics in HFM and their associations with clinical, seminal, and biochemical parameters. Methods: A cohort of 248 HFM (35.3 ± 5.9years) was studied, evaluating, on the same day, clinical, biochemical, seminal, and scrotal CDUS following Standard Operating Procedures. Results: The CDUS reference range and characteristics of the scrotal organs of HFM are reported here. CDUS showed a higher accuracy than physical examination in detecting scrotal abnormalities. Prader orchidometer (PO)‐ and US‐measured testicular volume (TV) were closely related. The US‐assessed TV with the ellipsoid formula showed the best correlation with the PO‐TV. The mean TV of HFM was ~ 17 ml. The lowest reference limit for right and left testis was 12 and 11 ml, thresholds defining testicular hypotrophy. The highest reference limit for epididymal head, tail, and vas deferens was 12, 6, and 4.5 mm, respectively. Mean TV was associated positively with sperm concentration and total count and negatively with gonadotropins levels and pulse pressure. Subjects with testicular inhomogeneity or calcifications showed lower sperm vitality and concentration, respectively, than the rest of the sample. Sperm normal morphology and progressive motility were positively associated with epididymal head size/vascularization and vas deferens size, respectively. Increased epididymis and vas deferens sizes were associated with MAR test positivity. Decreased epididymal tail homogeneity/vascularization were positively associated with waistline, which was negatively associated with intratesticular vascularization. CDUS varicocele was detected in 37.2% of men and was not associated with seminal or hormonal parameters. Scrotal CDUS parameters were not associated with time to pregnancy, number of children, history of miscarriage. Conclusions: The present findings will help in better understanding male infertility pathophysiology, improving its management.